P-713 Prescription determinants of intrauterine devices in different European countries - Results from the real-world safety study EURAS-LCS12. (30th June 2022) - Eggebrecht, L; Bauerfeind, A; Böhnke, T; Hagemann, C; Cellier, C; Lange, J; Heinemann, K
Abstract: Study question: What are the reasons for intrauterine devices (IUD) use beyond contraception for various IUD types in routine clinical practice across Europe? Summary answer: Beyond contraception, high- and low-dose levonorgestrel (LNG)-releasing IUDs are frequently used for heavy menstrual bleeding, especially in Mediterranean countries. What is known already: All IUDs are approved for the use of contraception, but additional indications differ by IUD type (i.e., LNG- and copper-containing). The higher, 52 mg LNG, dose IUD (e.g., Mirena) is also approved for the treatment of menorrhagia and endometrium protection during hormone replacement therapy. There is a documented off-label indication to use copper IUD as emergency contraception within 5 days of unprotected intercourse. The only approved indication for LNG-intrauterine devices containing less than 52 mg LNG (e.g., LCS12, Kyleena) is contraception. Study design, size, duration: EURAS-LCS12 is an ongoing prospective, non-interventional cohort study with active surveillance in ten European countries (Austria, Czech Republic, Spain, Sweden, Finland, Poland, Germany, United Kingdom, Italy, and France). Participants/materials, setting, methods: Women (N = 77, 088) with a newly inserted hormonal or copper IUD (i.e., LCS12, Kyleena, Mirena, copper IUD) were enrolled between 2014 and 2021 (planned interim stage). Information on reasons for IUD use was collected from the inserting health care professional, and multiple answers were possible. In 2016 the inclusion criteria were restricted to women below the age of 40 years. Main results and the role of chance: The most common reason for IUD use was birth control in all four cohorts (98.3% of LCS12, 98.4% of Kyleena, 93.4% of Mirena and 98.9% of copper IUD users). For LCS12, Kyleena and Mirena, heavy menstrual bleeding was reported as most frequent additional reason (9.0%, 11.6%, and 24.9%, respectively). Of all Mirena users, 5.5% received the prescription solely for the treatment of heavy menstrual bleeding without a need for contraception. For copper IUDs, emergency contraception was the most frequently reported additional reason in 2.2% of the women. There were differences with respect to country: In Italy, Austria, Spain, and France LCS12 and Kyleena were also prescribed for heavy menstrual bleeding with frequencies between 20% and 33%. The overall proportion for menorrhagia indication in Mirena users were in the ranges from 10% (Germany) to 58% (Italy). Copper IUDs were primarily used for contraception indications (98% to 100% across all countries). The rates for heavy menstrual bleeding as a reason for copper IUD use remained below 1% across all countries. The United Kingdom revealed the highest rate for emergency contraception usage in copper IUD users among all countries (i.e., 7%), followed by Germany with 2%. Limitations, reasons for caution: The cohort is mainly limited to women below the age of 40 years. Frequencies of reasons for IUD use beyond contraception, especially with respect to heavy menstrual bleeding might differ in women of higher age. Wider implications of the findings: Mirena is frequently used for its additional approved indication (i.e., menorrhagia). LCS12 and Kyleena are used for menorrhagia in addition to contraception, especially in Italy, Spain and Austria. It remains to be evaluated whether also low-dose LNG-IUDs are effective in treating idiopathic menorrhagia. Trial registration number: NCT02146950